2007
DOI: 10.1598/jaal.51.3.1
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Middle Schools: The Differences in Structure and Instruction

Abstract: A tale of two middle schools: The differences in structure and instruction A tale of two middle schools: The differences in structure and instructionThe way teachers use instructional time and the consistency with which they implement instructional strategies are two important variables that can affect student achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
3
9
0
1
Order By: Relevance
“…More specifically, and taking into account the uncertainty caused by the relatively high mean SE of Hispanic students using an 80-90 minute block all-year configuration, White, Black, and possibly Hispanic students in a 61-79 minute block all-year configuration earned the highest mean test scores. This finding coincides with previous research showing students perform better in block schedules with longer, concentrated periods of time than a traditional instructional time configuration (Candy & Rettig, 1995;Carroll, 1994;Childers & Ireland, 2005;Evans, 2005;Fisher & Frey, 2007;Gill, 2011;Gullatt, 2006). Also, research on social studies instruction shows that longer class periods allow teachers increased opportunities for group activities and in-class projects (Bryant & Bryant, 2000;DiBiase & Queen, 1999;Hamdy & Urich, 1998;Johnson & Johnson, 1989;Rofes, 2001;Wilson & Stokes, 2000) and to abandon lectures and utilize strategies more compatible with individualized instruction (Gullatt, 2006;Slavin et al, 1989;Wilson & Stokes, 2000).…”
Section: Research Questionsupporting
confidence: 91%
“…More specifically, and taking into account the uncertainty caused by the relatively high mean SE of Hispanic students using an 80-90 minute block all-year configuration, White, Black, and possibly Hispanic students in a 61-79 minute block all-year configuration earned the highest mean test scores. This finding coincides with previous research showing students perform better in block schedules with longer, concentrated periods of time than a traditional instructional time configuration (Candy & Rettig, 1995;Carroll, 1994;Childers & Ireland, 2005;Evans, 2005;Fisher & Frey, 2007;Gill, 2011;Gullatt, 2006). Also, research on social studies instruction shows that longer class periods allow teachers increased opportunities for group activities and in-class projects (Bryant & Bryant, 2000;DiBiase & Queen, 1999;Hamdy & Urich, 1998;Johnson & Johnson, 1989;Rofes, 2001;Wilson & Stokes, 2000) and to abandon lectures and utilize strategies more compatible with individualized instruction (Gullatt, 2006;Slavin et al, 1989;Wilson & Stokes, 2000).…”
Section: Research Questionsupporting
confidence: 91%
“…The alternating block schedule provides all teachers with the opportunity to offer the exploratory or elective classes and to use longer periods of time to provide richness in the curriculum (Hackmann & Valentine, 1998;National Education Commission on Time and Learning, 1994). Fisher and Frey (2007) found that traditional schedules do not promote child-centered instruction, nor is the academic success of students in the 45/55-minute schedule as good as those in the interdisciplinary block. Critics might say that meeting daily offers the advantage of seeing students more frequently and offering a small dose of instruction and thus is preferable to the alternating day schedule.…”
Section: Block and Traditional Schedulingmentioning
confidence: 88%
“…As students begin working within these groups, the social dynamic that outbursts or passive disengagement (Long, MacBlain, & MacBlain, 2007). Whether students are actively seeking ways out of the classroom or shutting down within, the achievement gap continues to widen (Fisher & Frey, 2007;Long et al, 2007).…”
Section: Conceptual Frameworkmentioning
confidence: 99%